Influence of aging on visual perception and visual motor integration in Korean adults - Kim, Eunhwi (Korean Society of Exercise Rehabilitation, 2014)
This study investigated age-related changes of cognitive function in Korean adults using the Korean-Developmental Test of Visual Perception-2 (K-DTVP-2) and the Visual Motor Integration-3rd Revision (VMI-3R) test, and determined the main factors influencing VP and VMI in older adults. For this research, 139 adults for the K-DTVP-2 and 192 adults for the VMI-3R, from a total of 283 participants, were randomly and separately recruited in province, Korea. The present study showed that the mean score of the K-DTVP-2 and VMI-3R in 10-yr age increments significantly decreased as age increased (K-DTVP-2, F= 41.120, P< 0.001; VMI-3R, F= 16.583, P< 0.001). The mean score of the VMI-3R and K-DTVP-2 were significantly decreased in participants in their 50s compared to those in their 20s (P< 0.05). Age (t= −9.130, P< 0.001), gender (t= 3.029, P= 0.003), and the presence of diseases (t= −2.504, P= 0.013) were the significant factors affecting K-DTVP-2 score. On the other hand, age (t= −6.300, P< 0.001) was the only significant factor affecting VMI-3R score. K-DTVP-2 score (Standardized β= −0.611) decreased more sensitively with aging than VMI-3R (Standardized β= −0.467). The two measurements had a significant positive correlation (r = 0.855, P< 0.001). In conclusion, it can be suggested that VP and VMI should be regularly checked from an individual’s 50s, which is a critical period for detecting cognitive decline by aging. Both the K-DTVP-2 and VMI-3R could be used for determining the level of cognitive deficit by aging.